Scoping Review: Manfaat Teknik Elevasi Kaki sebagai Intervensi Sederhana untuk Menurunkan Risiko Hipotensi Pasca Spinal Anestesi (Lembaga Pengembangan Kinerja Dosen, 2026)
Hypotension following spinal anesthesia is a frequent perioperative complication, particularly among pregnant patients, with an incidence ranging from 60% to 80%. This condition may compromise uteroplacental perfusion and pose serious risks to both mother and fetus. Leg elevation represents a simple, safe, inexpensive, and effective non-pharmacological intervention that functions through gravitational autotransfusion, enhancing venous return and improving cardiac output. This scoping review was conducted using the Joanna Briggs Institute (JBI) methodology and the PRISMA-ScR framework, guided by the PICO approach. The population included adult patients undergoing spinal anesthesia, with the intervention consisting of elevating the legs at an angle of 20–30° or approximately 30 cm for 10–15 minutes, compared with the standard supine position. Literature searches were performed through PubMed and Google Scholar, focusing on primary studies published within the last five years. Of the 130 articles identified, 10 met the inclusion criteria and were analyzed descriptively. The findings demonstrate that leg elevation significantly increases systolic and diastolic blood pressure as well as mean arterial pressure (MAP), while reducing the incidence of post-spinal hypotension. The technique also decreases vasopressor requirements without notable adverse effects, particularly in obstetric populations. Based on the available evidence, leg elevation is recommended as an effective and feasible initial non-pharmacological strategy for preventing hypotension after spinal anesthesia, especially in resource-limited clinical settings, with an optimal elevation of 20–30° for 10–15 minutes.